2023
DOI: 10.3390/ijerph20085498
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of 12-Week Dual-Task Physical–Cognitive Training on Gait, Balance, Lower Extremity Muscle Strength, and Cognition in Older Adult Women: A Randomized Study

Abstract: This study aims to investigate the effects of dual-task physical–cognitive the training on body balance (BB), gait performance (GP), lower limb muscle strength (LEMS), and cognitive performance (CP) in a group of cognitively normal older adult women (n = 44; 66.20 ± 4.05 years). Of these, 22 were randomly allocated to the dual-task training (DT) group, and 22 participated in the control group (CG). Assessments were performed at baseline, after 12 weeks of intervention, and at the end of 12 weeks of follow-up, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 107 publications
0
5
0
Order By: Relevance
“…A total of 11 studies [20,[30][31][32][33][34][35][36][37][38][39] were finally included. All studies chose the cognitivemotor MT mode, and most of the intervention programs were in the form of DT balance training combined with cognitive tasks such as counting, memorizing, naming and video games, etc.…”
Section: Conceptual Descriptionmentioning
confidence: 99%
See 4 more Smart Citations
“…A total of 11 studies [20,[30][31][32][33][34][35][36][37][38][39] were finally included. All studies chose the cognitivemotor MT mode, and most of the intervention programs were in the form of DT balance training combined with cognitive tasks such as counting, memorizing, naming and video games, etc.…”
Section: Conceptual Descriptionmentioning
confidence: 99%
“…Only one study [38] reported the use of MT training (e.g., walking to music and responding to changes in the rhythmic patterns of the music). In terms of intervention duration, six studies [20,30,[33][34][35]39] reported intervention durations of 3 to 6 months, four studies [31,32,36,37] reported intervention durations shorter than 3 months, and one MT training study [38] reported a 6-month intervention. Meanwhile, in terms of intervention frequency, 10 study protocols used a frequency of one to three times per week, and only 1 study [39] opted for DT training five times a week.…”
Section: Conceptual Descriptionmentioning
confidence: 99%
See 3 more Smart Citations